Interactive Multimedia Application of Teaching Style as a Learning Medium for Physical Education Teachers - Agus Salim Samosir; Imran Akhmad; Bangun Setia Hasibuan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The research aims to produce a teaching style application product in health sports Physical Education (PE) teachers based on interactive multimedia. This research is expected to overcome difficulties for Physical Education teachers who have been on the use of teaching styles carried out by Physical Education teachers only centered on teachers continuously and have not fully applied variations in teaching styles so that it causes learners to become bored and can inhibit the potential that exists in learners. In other respects, the lack of knowledge that Physical Education teachers have on teaching style, and the low interest of teachers to read books and find sources for teaching styles. The research stages are; (1) The pre-development stage, at this stage, needs analysis is carried out through a survey of the level of tool needs for users, instrument preparation and consultation with experts. (2) The development phase of developing the product "Teaching Style Application" starting from the initial product development of manuscripts (manuals), designing work and application design, small group trials, stage I improvements, large group trials, phase II improvements, mass production. (3) The evaluation stage of product results implementation and product desimination.